ARKEOLOGI NATUNA : KORIDOR MARITIM DI PERAIRAN LAUT CINA SELATAN - Sonny C. Wibisono (Badan Riset dan Inovasi Nasional, 2014)
One of the interesting historical episodes to be observed during the period of growth and development of Śrīvijaya is the long distance commercial activity. Chinese chronicles quite clearly note that the kingdom’s headquarters in Sumatera has sent more than twenty commercial missions to China between 10th–13th Century, and vice versa. The waters of the South China Sea region were more and more intensively sailed at that time. The focus of attention in this paper is the study of archeology in the archipelago, especially in the South China Sea, which is worth to be studied in search of the path of long-distance commerce between China and the archipelago, especially in relationto the Śrīvijaya period. In addition to the ports along the coast of Mainland Southeast Asian continent, in fact there are many small islands that were likely to be a “stepping stone” in the course of trade which have escaped the attention, such as Paracel Islands, Spratley, Anambas, and Natuna. Natuna Islands is one of a cluster of small islands facing the South China Sea, occupying a crossing place into the waters of Malacca, Sumatera, and Borneo. In this paper will be presented archaeological evidence, the results of the survey and excavation in Natuna during 2012-2014, including data on the site and artifacts. Ceramics as an indicator of commerce is specially analyzed (both qualitatively and quantitatively) for comparison. Salah satu episode sejarah yang menarik untuk dicermati selama masa pertumbuhan dan perkembangan Śrīwijaya adalah berlangsungnya kegiatan niaga jarak jauh. Dalam kronik Cina cukup jelas dicatat, kerajaan yang pusatnya di Sumatera ini, telah mengirimkan lebih dari dua puluh misi perniagaan ke Cina antara abad ke-10-13 M., demikian pula sebaliknya. Kawasan perairan Laut Cina Selatan, merupakan jalur yang semakin intensif dilalui pada masa itu. Permasalahan yang menjadi fokus perhatian dalam tulisan ini tentang studi arkeologi di wilayah kepulauan khususnya di Laut Cina Selatan yang dipandang patut diteliti untuk menelusur jejak jalur perniagaan jarak jauh antara Cina dan Nusantara, terutama hubungannya dengan masa Śrīwijaya. Di samping penelitian terhadap bandar-bandar di sepanjang pantai Benua Asia Tenggara Daratan, pada kenyataan banyak kepulauan kecil yang sangat mungkin menjadi “batu loncatan” dalam perjalanan niaga yang selama ini luput dari perhatian seperti Kepuluan Paracel, Spratley, Anambas, dan Natuna. Pulau ini merupakan salah satu gugusan pulau-pulau kecil yang berhadapan dengan Laut Cina Selatan, menempati posisi persilangan jalur untuk memasuki perairan Malaka, Sumatera, dan Kalimantan. Dalam tulisan ini akan disajikan bukti-bukti arkeologis, dari hasil survei dan ekskavasi Natuna tahun 2012-2014, termasuk data situs dan artefaktual. Keramik sebagai indikator perniagaan dianalisis khusus (kualitatif dan kuantitatif) untuk perbandingan.